The John Zink Hamworthy combustion handbook. Volume 3, - Baukal, Charles E., Jr., 1959- (Industrial combustion series., 2013)
Process BurnersErwin Platvoet, I-Ping Chung, Michael Claxton, and Tami FischerOil BurnersI-Ping Chung, Steve Londerville, Mike Claxton, and Bill JohnsonBurners and Combustion for Industrial and Utility BoilersVladimir LifshitsDuct BurnersPeter F. Barry, Stephen L. Somers, and Steve LondervilleProcess HeatersErwin Platvoet, David Brown, and Rasik PatelAir HeatersCarl Connally, Lothar Schulz, and Tim WebsterThermal Oxidizer BasicsBernd Reese, Wolfgang Klaus, and Jay KaranThermal Oxidizer Control and ConfigurationsBernd Reese, Wolfgang Klaus, Jay Karan, and Juergen FoeltingSelected Pollution Control EquipmentKlaus-Dieter ZschorschFlaresRobert Schwartz, Jeff White, and Wes BussmanFlare Ignition SystemsJ. Bellovich, J. Franklin, and Charles E. Baukal, Jr. Biogas FlaringTim Locke and Brandy JohnsonFlare Gas RecoveryJim Peterson, Nick Tuttle, Harley Cooper, and Charles E. Baukal, Jr. Hydrocarbon Vapor Control TechnologyRoger E. BlantonMarine and Offshore ApplicationsRichard PriceIndex.